1988
DOI: 10.1016/s0005-7894(88)80057-1
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies for working women: Aerobic exercise and relaxation interventions

Abstract: In presenting this thesis in partial fulfilment of the requirements for an advanced degree at the The University of British Columbia, I agree that the Library shall make it freely available for reference and study. I further agree that permission for extensive copying of this thesis for scholarly purposes may be granted by the Head of my Department or by his or her representatives. It is understood that copying or publication of this thesis for financial gain..shall not be allowed without my written permission. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 16 publications
2
24
2
Order By: Relevance
“…In this way it is unlike constructs, such as self-esteem, that describe a general state of being. Notwithstanding this theoretical assumption about self-efficacy, a number of studies (see, e.g., Long and Haney, 10 Sherer et al 11 ) have tried to measure the amount of self-efficacy expressed by individuals about themselves in a general way. These efforts should likely not be construed as a true test of the construct.…”
Section: Self-efficacy Is Behavior Specificmentioning
confidence: 99%
“…In this way it is unlike constructs, such as self-esteem, that describe a general state of being. Notwithstanding this theoretical assumption about self-efficacy, a number of studies (see, e.g., Long and Haney, 10 Sherer et al 11 ) have tried to measure the amount of self-efficacy expressed by individuals about themselves in a general way. These efforts should likely not be construed as a true test of the construct.…”
Section: Self-efficacy Is Behavior Specificmentioning
confidence: 99%
“…A decrease in anxiety levels after the implementation of sport psychological interventions is not a strange phenomenon. Long (1984) and Long and Haney (1988) found that anxiety levels of joggers decreased significantly after stress-inoculation and progressive relaxation exercises. Kingston and Hardy (1997) found that process goals set by golf players have a positive effect on their self-efficacy, cognitive anxiety and self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…People are not self-efficacious in general; rather their sense of efficacy is tied to particular behaviors and the situational context in which they occur. However, Sherer and Maddux (1982) and Long and Haney (1988) view self-efficacy as a general concept based on a broader sense of peoples' ability to perform a range o f actions in a variety of situations well. According to this more general view, self-efficacy is learned early in life and changes little during adulthood.…”
Section: Self-efficacvmentioning
confidence: 99%